2018 15th International Symposium on Wireless Communication Systems (ISWCS) 2018
DOI: 10.1109/iswcs.2018.8491095
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Backscatter Communication: A New Paradigm

Abstract: In this paper, we propose a novel quantum backscatter communications (QBC) protocol, inspired by the quantum illumination (QI) concept. In the QBC paradigm, the transmitter generates entangled photon pair. The signal photon is transmitted and the idler photon is kept at the receiver. The tag antenna communicates by performing the pulse amplitude modulation (PAM), binary phase shift keying (BPSK) or quadratic phase shift keying (QPSK) on the signal impinging at the antenna. Using the sum-frequency-generation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…We will assume that the retention process is carried out by a memory element that can be modelled accurately by a pure loss channel. This new treatment is a little bit different from earlier ones [15][16][17], where the idler mode was assumed to be retained losslessly at the receiver. The tag antenna can be modelled by a low reflectivity beamsplitter, where thermal noise enters from the beamsplitter's dark port.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…We will assume that the retention process is carried out by a memory element that can be modelled accurately by a pure loss channel. This new treatment is a little bit different from earlier ones [15][16][17], where the idler mode was assumed to be retained losslessly at the receiver. The tag antenna can be modelled by a low reflectivity beamsplitter, where thermal noise enters from the beamsplitter's dark port.…”
Section: Introductionmentioning
confidence: 94%
“…Notable efforts have been made in the field of microwave quantum communication, the most renowned among them are microwave quantum teleportation [12] and quantum illumination enhanced sensing [13,14]. In this paper we will focus on a new application in which quantum approaches can be used for improved sensitivities and resolutions, namely, quantum backscatter communication (QBC) [15][16][17]. Quantum backscattering is a branch of quantum communication, which exploits quantum entanglement in order to distil backscattered signals propagating through a noisy thermal channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we can conclude that the HOM receiver is a unitary linear receiver that preserves the total number of photons. On the other hand, the interaction Hamiltonian describing the sum frequency receiver is expressed as [2], [3] :…”
Section: Feasibility Of the Detection Processmentioning
confidence: 99%
“…Quantum entanglement, whereby distant systems exhibit non-local measurement correlations, holds the keys to realizing precision measurements that go beyond the classical shot noise limit. By harnessing these non-classical correlations recent protocols had been developed to detect targets submersed in noisy and lossy environment [6], while recently the same concept was deployed to detect backscattered communication signals in the microwave regime [1], [2]. Moreover, it had been shown that target detection using entangled photon pairs is optimal under the same environmental assumptions [6]- [8].…”
Section: Introductionmentioning
confidence: 99%